Penerapan Customer Relationship Manajemen (CRM) Untuk Meningkatkan Loylitas Pelanggan Pada Pt.Rekind Daya Mamuju - Ramadhani, Ainaya Ifditiya; Yeni, Hari (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
This study aims to assess the implementation of Customer Relationship Management (CRM) in increasing customer loyalty at PT Rekind Daya Mamuju (RDM), a company that focuses on the operation and maintenance of a 2x25 MW Steam Power Plant (PLTU) located in Mamuju Regency, West Sulawesi. In the power generation sector, service continuity and operational reliability are highly dependent on the quality of interactions between service providers and customers, thus CRM plays a crucial role in building trust and long-term loyalty. This study used a quantitative method with a survey conducted on 60 customers who interact directly with PT RDM in the operation and maintenance of the plant. Data were obtained through a questionnaire with a five-point Likert scale that assessed the dimensions of CRM, including service quality, communication, responsiveness, and complaint handling, as well as customer loyalty consisting of satisfaction, trust, reuse of services, and willingness to recommend the company. The data analysis process was carried out using descriptive statistics and simple linear regression. The results of the study indicate that the implementation of CRM at PT RDM is at a good level, especially in the aspects of speed of response to problems at the plant and staff professionalism. In addition, the level of customer loyalty is also relatively high, indicated by high satisfaction and trust in the company. The results of the regression test indicate that CRM has a positive and significant impact on customer loyalty. This finding suggests that the better the relationships and services provided by PT RDM, the higher the customer loyalty. Therefore, PT RDM needs to continue strengthening its CRM strategy to maintain working relationships and increase the company's competitiveness in the power generation services sector.